Penguasaan Leksikal Pada Anak Tk dan Paud Tunas Kori Dharma di Denpasar: Kajian Psikolinguistik - Rabiatun Nur Annisa, Siti; Suparwa, I Nyoman; Teguh, I Wayan (Humanis, 2016)
This thesis entitled " Mastery of Lexical on Children in kindergarten and early childhood education at Kori Dharma Tunas school at Denpasar: Psycholinguistics Studies" motivated by the process of acquisition and mastery of objects that shown into children under five years old. This research discussed about two problems; the vocabulary mastered by children under five years old and the factors that affect the lexical mastery by each child. The aims of this study were to determine the vocabulary mastered by children under five years old and also the factors that influence the lexical mastery . This study uses three methods and techniques: methods and data collection techniques, methods and data processing techniques, and methods of data analysis and presentation techniques.  Two theories are used on this study the theory of semantic features hypotheses, and theories of child development. This study found that there are two types of words which mastered by the children, namely: nouns and verbs. Children could mention noun words such as strawberries, avocados, oranges, shoes, mosquito, cars, fish, sheep, laying kite, giraffes, wine, and monkey, then for the verb, they could mention walking, reading, swimming, rake and watering. Kid’s lexical development influenced by two factor; age and environmental.